The Female and Women in Origen - Stratis, Vasileios (Dia-noesis: A Journal of Philosophy, 2025)
Origen of Alexandria, the prolific Christian theologian and philosopher of the 3rd century, presents an interesting anthropology regarding genders. This article will endeavour to outline his approach to the topic of genders, more specifically to his portrayal of the female in relation to the male and his original theory of the transcendence of sexes and genders both in his protology and in his eschatology or in his exegesis of biblical literature. But is this theory as subversive as it appears to be when it comes to the stereotypical picture of the female and women at his time? Can his ‘angelic’ prototype be related to modern gender theories? Are women and the feminine exalted in his anthropology or still remain in their traditional framework?